1969
DOI: 10.1177/001872086901100413
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Movement Time Between Brake and Accelerator Pedals in Automobiles

Abstract: This report represents the results of a preliminary study to determine if there is a valid cause to question the positional relationship of brake and accelerator pedals in contemporary automobiles. Ten subjects were tested to determine how long it takes to move the foot from the accelerator to the brake pedal (a) in the same horizontal plane, and (b) with a 6-in. height differential. Experimental results indicated that at high speeds, a reduction in stopping distance of upwards of 14 ft. could be affected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The mean time savings of 0.13 sec. in the use of the hand control can be accounted for by the elimination of the movement time between pedals (Davies and Watts, 1969). Thus, the presence of the hand on the brake control is a significant factor in reducing the total reaction time, as has been implied, although apparently not measured, in the past (Ward and Gingras, 1956).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean time savings of 0.13 sec. in the use of the hand control can be accounted for by the elimination of the movement time between pedals (Davies and Watts, 1969). Thus, the presence of the hand on the brake control is a significant factor in reducing the total reaction time, as has been implied, although apparently not measured, in the past (Ward and Gingras, 1956).…”
Section: Discussionmentioning
confidence: 98%
“…cluding a pistol grip control in which the trigger I activates the brakes (Mayyasi, Pulley, and The distance travelled by a vehicle at high speeds in small time intervals is quite large and, as has been pointed in previous studies of driver's response times (Davies and Watts, 1969;1970; Johansson and Rumar, 1971), small Mvings in the time required to activate a vehicle's brakes could be important in reducing the 11.8% of accidents attributed to "following too closely" (Accident Facts, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…A simulated driving situation was used by Neal (1946) to determine the time required by subjects to apply the brakes of their vehicle under hazardous conditions, Other studies have been conducted in recent years. Watts (1969 and1970) investigated the relationships of pedal placement on brake reaction time and seat height and pedal placement on brake reaction time. Lisper, et al (1968) studied the effect of light and sound stimuli and the factor of fatigue on driver reactions.…”
Section: Introduction General Discussionmentioning
confidence: 99%
“…Some drivers tended to prefer frequent braking actions, (e.g., driver #42 with 12.27% braking actions); others tended to brake less often (e.g., driver #8 with 1.43% braking actions). When we preprocessed data, the driver's movement time -the time to lift the foot off the accelerator pedal, move it laterally to the brake pedal, or vice versa -was not considered because the performance time was very small (about 0.15 -0.30 seconds [47]), compared to the total driving time and the time of keeping their foot on the brake pedal. We also found that drivers would not always put their foot on the brake pedal and gas pedal, but the duration was very small, compared to the total car-following time (with a percentage of about 1.873 × 10 −4 in our experiments).…”
Section: General Data Analysismentioning
confidence: 99%